Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Pd-iminocarboxylate complexes and their behavior in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Gonnade, Rajesh G.; Pandole, Satish P.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2020)
Designing co-catalyst-free late transition metal complexes for ethylene polymerization is a challenging task at the interface of organometallic and polymer chemistry. Herein, a set of new, co-catalyst-free, single-component catalytic systems for ethylene polymerization have been unraveled. Treatment of anthranilic acid with various aldehydes produced four iminocarboxylate ligands (L1-L4) in very good to excellent yield (75-92 %). The existence of 2-((2-methoxybenzylidene)amino) benzoic acid (L1) has been unambiguously demonstrated using NMR spectroscopy, MS and single-crystal X-ray diffraction. A neutral Pd-iminocarboxylate complex [N OPdMe(L1)] (N O=kappa(2)-N,O-ArCHNC6H4CO2 with Ar=2-MeOC6H4) C1 was prepared by treating stoichiometric amount of L1.Na with palladium precursor. The identity of C1 was confirmed by 1-2D NMR spectroscopy and single-crystal X-ray diffraction studies. Along the same lines, palladium complexes C2-C4 were prepared from ligands L2-L4 respectively. In-situ high-pressure NMR investigations revealed that these Pd complexes are amenable to ethylene insertion and undergo facile beta-H elimination to produce propylene. These palladium complexes were then evaluated in ethylene polymerization reaction and various reaction parameters were screened. When C1-C4 were exposed to ethylene pressures of 10-50 bar, formation of low-molecular-weight polyethylene was observed.
Keywords: imine; Imine-carboxylate; Insertion polymerization; Pd complexes; Polyethylene